2022
DOI: 10.4103/jpbs.jpbs_170_22
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Corticotomy and Piezocision in Orthodontic Canine Retraction

Abstract: Background: There have been many studies and experiments to evaluate the effectiveness of different types of dental treatment. Maxillary canine extraction is such a dental treatment which can be performed through either alveolar corticotomy (AC) or piezocision (PZ). The current study aims to compare the effectiveness of these two types of dental procedures. It is based on a randomized clinical trial (RCT) through the split-mouth technique supported by a parallel group design. The participants in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…It was also observed that there was a decrease in treatment time after piezocision. However, the article by Sonone and Nawab [20] concluded that piezocision and corticotomy are not effective in accelerating canine retraction as there was no statistically significant difference from the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that there was a decrease in treatment time after piezocision. However, the article by Sonone and Nawab [20] concluded that piezocision and corticotomy are not effective in accelerating canine retraction as there was no statistically significant difference from the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Table S1: Search strategy of the online databases; Table S2: Excluded studies from full-text reading; Table S3: Risk of bias. References [60][61][62][63][64][65][66][67][68][69] are cited in Table S2.…”
Section: Supplementary Materialsmentioning
confidence: 99%